Modularize Formatting Objects learn how to create flexible, reusable formatting objects stylesheets. - Beugebauer, Frank
The Extensible Stylesheet Language (XSL) W3C recommendation was created as a means to display XML data. The recommendation includes a transformation language (XSLT) and formatting objet for output format) language (XSL-FO), which together provide the XSL stylesheet developer with the tools necessary to present XML.